2010
DOI: 10.1039/c0sm00009d
|View full text |Cite
|
Sign up to set email alerts
|

Nano-hybrid self-crosslinked PDMA/silica hydrogels

Abstract: We discovered that the free radical polymerization of N,N-dimethylacrylamide in water can lead, above a certain concentration, to gels without any added difunctional crosslinker. These so called ''selfcrosslinked'' hydrogels were prepared and their weak mechanical properties were improved by introducing silica nanoparticles. From swelling experiments performed at equilibrium in aqueous media, it was shown that silica particles behave as adhesive fillers and strongly interact with PDMA chains. These interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
144
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(154 citation statements)
references
References 57 publications
10
144
0
Order By: Relevance
“…Tensile tests were carried out and repeated as a standard test with a strain rate of 100 mm/min ( ε &~0.06s -1 ) at a room temperature. Tensile properties of nanosilica PDMA gels are seen to strongly depend on silica content [10], In the first part of the curve, at low strains (ε<0.03), the initial modulus E is defined and identified as the Young's modulus. Experimental Young's moduli are given in Table 2.…”
Section: A Tensile Behaviour: General Shape and Modulusmentioning
confidence: 99%
“…Tensile tests were carried out and repeated as a standard test with a strain rate of 100 mm/min ( ε &~0.06s -1 ) at a room temperature. Tensile properties of nanosilica PDMA gels are seen to strongly depend on silica content [10], In the first part of the curve, at low strains (ε<0.03), the initial modulus E is defined and identified as the Young's modulus. Experimental Young's moduli are given in Table 2.…”
Section: A Tensile Behaviour: General Shape and Modulusmentioning
confidence: 99%
“…In the case of hybrid hydrogels prepared by cross-linking polymerization of DMA in silica suspension, we have shown that the presence of silica nanoparticles greatly enhances the whole mechanical properties [17,[19][20] . Interestingly, both initial modulus, dissipation, nominal strain at break and fracture energy were seen to be simultaneously enhanced with increasing amount of silica.…”
Section: Introductionmentioning
confidence: 98%
“…[1] Despite their wide potential in biomedicine and industry, [2,3] applications of these aqueous-based soft materials have long been restricted due to their intrinsic poor mechanical strength, mainly related to the high hydration level and low efficiency of dissipation process. Since the last 15 years, different efficient strategies have been developed to improve their mechanical properties with either introducing inorganic charges forming nanocomposites or hybrid hydrogels [4,5] or using smart macromolecular architectures such as double network systems, [6] slide-ring gels, [7] or tetra-PEG. [8] During the past few years, another mode of hydrogel reinforcement based on the universal concept of polymer phase separation has been developed.…”
Section: Introductionmentioning
confidence: 99%